The Design and Implementation of Deposit Insurance Systems - Hoelscher, David; Klueh, Ulrich; Taylor, Michael (Washington, D.C. : International Monetary Fund, 2006)
This paper describes recently established deposit insurance systems, identifying emerging trends. In line with previous IMF work on the subject, it argues against the development of "best practices" applicable to all systems. Rather, it stresses the importance of incorporating each country's individual objectives in adopting a deposit insurance system, as well as that country's characteristics, to ensure an effective system that minimizes disincentives and distortions to financial sector intermediation. The paper includes a summary of the academic literature.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet